Wind Stress-Induced Multiyear Predictability of Annual Sea Surface Temperature Anomalies in the Extratropical North Atlantic - Reintges, Annika (Zenodo, 2021)
Workshop: Multi-annual to Decadal Climate Predictability in the North Atlantic-Arctic Sector